The inflation situation in Hungary: Response to Katalin Botos „Inflation and our finances” and István Ábel – Gergely Bognár – Máté Lóga – Attila István Szabó „Changes in the explanation of inflation” - Varga, József; Sipiczki, Zoltán (Public Finance Quarterly, 2024)
The article examines the factors driving inﬂation in 2022-2023. We explore why inﬂation in the Hungarian economy has risen more sharply compared to neighboring countries with similar economic structures. The goal of the article is to highlight these factors and provide policymakers with recommendations for a more resilient inﬂation policy.First, we respond to Katalin Botos’ views on inﬂation, and then we analyze some global inﬂationary trends. Our study focuses speciﬁcally on inﬂation in the agricultural sector.Our ﬁndings indicate that, in addition to global cost-push inﬂationary pressures, several country-speciﬁc factors have contributed to the rise in domestic inﬂation. Energy prices have surged, and some supply chains in the East have been disrupted. For Hungary’s less productive but energy-intensive food industry, the energy price shock, combined with higher exchange rate volatility in 2022-2023 compared to neighboring countries, has had a strong impact in the short to medium term, causing signiﬁcant deviations from long-term equilibrium. In our view, beyond enhancing food self-sufficiency, special attention should be given to the domestic development of the agricultural supply chain.